(untitled) (Revista Internacional de Folkcomunicação, 2021)
This work reflects the concept of Tradition developed by Gilmar de Carvalho’s research. Based on this framework, we call upon your understanding of the approach to cordel poetry as a cultural phenomenon and discussed in the field of Communication. Therefore, this text brings a bibliographical review that dialogues with the researcher’s own work and makes propositions around a theoretical deepening of the brazilian cordel. We observe that, for Carvalho, Tradition is a fusion of times, impossible to be apprehended in a linear reading.